The Impact of Altitude at Birth on Perinatal Respiratory Support for Neonates with Trisomy 21 - Bloom, Jessica L.; Furniss, Anna; Suresh, Krithika; Fuhlbrigge, Robert C.; Lamb, Molly M.; Rosenberg, Sophie; Edwards, Anastasia; O'Leary, Sean T. (American Journal of Perinatology, 2021)
Objective Both high altitude and trisomy 21 (T21) status can negatively impact respiratory outcomes. The objective of this study was to examine the association between altitude and perinatal respiratory support in neonates with T21 compared with those without T21.Study Design This retrospective cohort study used the United States all-county natality files that included live, singleton, in-hospital births from 2015 to 2019. Descriptive statistics for neonates with and without the primary outcome of sustained assisted ventilation (>6 hours) were compared using t-tests and Chi-squared analyses. Multivariable logistic regression was used to determine the association between respiratory support and the presence of T21, and included an interaction term to determine whether the association between respiratory support and the presence of T21 was modified by elevation at delivery.Results A total of 17,939,006 neonates, 4,059 (0.02%) with T21 and 17,934,947 (99.98%) without, were included in the study. The odds of requiring sustained respiratory support following delivery were 5.95 (95% confidence interval [CI]: 5.31, 6.66), 4.06 (95% CI: 2.39, 6.89), 2.36 (95% CI: 1.64, 3.40), and 5.04 (95% CI: 1.54, 16.54) times as high for neonates with T21 than without T21 when born at low, medium, high, and very high elevations, respectively. The odds of requiring immediate ventilation support following delivery were 5.01 (95% CI: 4.59, 5.46), 5.90 (95% CI: 4.16, 8.36), 2.86 (95% CI: 2.15, 3.80), and 12.08 (95% CI: 6.78, 21.51) times as high for neonates with T21 than without T21 when born at low, medium, high, and very high elevation, respectively.Conclusion Neonates with T21 have increased odds of requiring respiratory support following delivery when compared with neonates without T21 at all categories of altitude. However, the odds ratios did not increase monotonically with altitude which indicates additional research is critical in understanding the effects of altitude on neonates with T21.Key Points
Keywords: trisomy 21; Down syndrome; altitude; elevation; respiratory support; neonate